Properties of concrete containing waste expanded polystyrene and natural resin - Kaya, Ayse; Kar, Filiz (Elsevier Sci Ltd, 2016)
In this study, the waste expanded polystyrene (EPS) was used in a mixture of cement and tragacanth resin in order to produce a new concrete material. The amount of the resin in the mixture was 0.5%, 1% and 1.5% of the total cement + EPS. The EPS ratios in the samples were determined as 20%, 40%, 60% and 80% of the total volume. The new samples were subjected to some tests to find out some thermal and mechanical properties. It was concluded that, when EPS ratios and resin ratios of the samples increased, the density, thermal conductivity, compressive strength and tensile strength decreased, and the porosity increased. The change in the physical properties shows that, some artificial pores (except from EPS's pores) are formed in concrete blocks which allow to increase the insulation characteristic of the material. As a result, it was recommended that; using EPS aggregated and resin-added concrete, (i) the waste EPS can be evaluated and environmental pollution can be prevented, (ii) the new produced samples can be used as partition walls, floorings, ceiling concretes, briquettes or bricks and plaster instead of building carrier systems such as columns or beams and by this the load of the building can be decreased. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Expanded polystyrene waste; Tragacanth; Light concretes; Insulation materials